Fitness of B-Cell Responses to SARS-CoV-2 WT and Variants Up to One Year After Mild COVID-19 – A Comprehensive Analysis - Meyer, Benjamin; Martinez-Murillo, Paola Andrea; Lemaitre, Barbara; Blanchard-Rohner, Géraldine; Didierlaurent, Arnaud M.; Fontannaz, Paola; Eugercios Manzanas, Chloé; Lambert, Paul-Henri; Loevy, Natasha; Kaiser, Laurent; Sartoretti, Julie; Tougne, Chantal; et al. (Frontiers in Immunology, 2022)
Objective To comprehensively evaluate SARS-CoV-2 specific B-cell and antibody responses up to one year after mild COVID-19. Methods In 31 mildly symptomatic COVID-19 participants SARS-CoV-2-specific plasmablasts and antigen-specific memory B cells were measured by ELISpot. Binding antibodies directed against the proteins spike (S), domain S1, and nucleocapsid (N) were estimated using rIFA, ELISA, and commercially available assays, and avidity measured using thiocyanate washout. Neutralizing antibodies against variants of concern were measured using a surrogate-neutralization test. Results Plasmablast responses were assessed in all participants who gave sequential samples during the first two weeks after infection; they preceded the rise in antibodies and correlated with antibody titers measured at one month. S1 and N protein-specific IgG memory B-cell responses remained stable during the first year, whereas S1-specific IgA memory B-cell responses declined after 6 months. Antibody titers waned over time, whilst potent affinity maturation was observed for anti-RBD antibodies. Neutralizing antibodies against wild-type (WT) and variants decayed during the first 6 months but titers significantly increased for Alpha, Gamma and Delta between 6 months and one year. Therefore, near-similar titers were observed for WT and Alpha after one year, and only slightly lower antibody levels for the Delta variant compared to WT. Anti-RBD antibody responses correlated with the neutralizing antibody titers at all time points, however the predicted titers were 3-fold lower at one year compared to one month. Conclusion In mild COVID-19, stable levels of SARS-CoV-2 specific memory B cells and antibodies neutralizing current variants of concern are observed up to one year post infection. Care should be taken when predicting neutralizing titers using commercial assays that measure binding antibodies.